Early career psychiatrists’ perceptions of and training experience in electroconvulsive therapy: A cross-sectional survey across Europe - Cristiana Țăpoi; Laith Alexander; Renato de Filippis; Agorastos Agorastos; Diogo Almeida; Gautam Bhatia; Gamze Erzin; Martyna Ewa Gołębiewska; Enita Metaj; Sara Medved; Krista Mieze; Miloš Milutinović; et al. (European Psychiatry)
Abstract Background Electroconvulsive therapy (ECT) is a safe and effective treatment for several major psychiatric conditions, including treatment-resistant depression, mania, and schizophrenia; nevertheless, its use remains controversial. Despite its availability in some European countries, ECT is still rarely used in others. This study aims to investigate the experiences and attitudes of early career psychiatrists (ECPs) across Europe towards ECT and to examine how their exposure to ECT influences their perceptions.